Sustainable Leadership, Environmental Turbulence, Resilience, and Employees' Wellbeing in SMEs - Iqbal, Qaisar; Piwowar-Sulej, Katarzyna (Frontiers in Psychology, 2022)
Drawing on the conservation of resources theory and contingency theories of leadership, this study aims to investigate how sustainable leadership (SL) influences employees’ well-being (WB) through employee resilience (ER) and to examine the moderating effect of environmental turbulence (ET) on the “sustainable leadership-employees’ well-being” relationship. Data was collected from 593 employees and 373 supervisors adopting two-wave design among small and medium-sized enterprises (SMEs) in China. The authors used structural equation modelling to empirically test the hypothesized model in this study. The research shows that SL is significantly related to the employee WB in SMEs. Regarding mediating effect, SL also indirectly influences employee WB through ER. Moreover, the impact of SL on employees’ WB becomes more prominent in the presence of lower ET. To the best of the authors’ knowledge, no prior study is available about the integrated relationship of SL, ER, ET and employee WB.